Expression of Cathepsin P mRNA, Protein and Activity in the Rat Choriocarcinoma cell line, Rcho-1, During Giant Cell Transformation - Hassanein, Mohamed (2007)
Lysosomal proteases perform critical functions in protein turnover and are essential for normal growth and development. Cathepsin P is a member of a newly discovered family of lysosomal cysteine proteases uniquely expressed in rodent placenta (PECs), and is closely related to human cathepsin L. Using the rat choriocarcinoma cell line model, Rcho-1, mRNA for the PECs cathepsins P, M, Q, R, 1, 2 was found to increase in expression during differentiation into a trophoblast giant cell phenotype. By contrast, expression of cathepsin L was not regulated. A specific enzyme assay was developed to show that activity of cathepsin P mirrored mRNA expression during differentiation. Cathepsin P protein co-localizes with cathepsin B, indicating that the enzyme probably functions in the endosomal-lysosomal compartment. This study demonstrates that the PEC genes produce functional proteases that can perform specific placental roles that are probably performed by broader specificity proteases in human placenta.